THE EFFECT OF ORGANIZATIONAL FACTORS ON PATIENT SECURITY INCIDENT REPORTING THROUGH INDIVIDUAL FACTORS - Rahmawati, Anna; Rudijanto, Achmad; Astari, Asti Melani (Jurnal Aplikasi Manajemen, 2018)
This study was conducted to determine the influence of organizational factor, individual factor towards safety patient incident reports, and the influence of organizational factor toward PSI reports through individual factors. This study method was a quantitative cross-sectional. The population is nurses. The sample is determined by purposive sampling, with its quantity is determined based on Slovin formula. The data was analyzed by Partial Least Square (PLS) using SMART PLS program. The result shows that organizational factor has a positive effect toward individual factor, individual factor have a positive effect towards PSI reports, organizational factors have a positive effect towards PSI report, and organizational factors have a positive effect towards PSI report through individual factor. The organizational factor is the most dominant. Manajemen can improve the policies related to the organizational factors by not excluding individual factors.